Pengembangan Media Pembelajaran Video Animasi Karakter Islami di Madrasah Ibtidaiyah - Kasrah; Firman; Sukmawaty (South Sulawesi Education Development, 2024)
The research on the Development of Islamic Character Animation Video Learning Media on the Material of Various Jobs aims to determine the needs analysis, planning, development and distribution of Islamic character animation video learning media on the material of Various Jobs. Product development uses the Research and Development (R&D) method with the 4D model: Define, Design, Development, and Disseminate. Data collection techniques include observation, interviews, questionnaires, and documentation. This study produced a learning video that was considered valid by language experts (89.28%), material experts (95.45%), and design experts (75%). This learning video is also practical for use by teachers (100%) and students (94.46%) and effective (92.85%). From the results of the study, it can be concluded that the Islamic character learning video is feasible, practical, and effective for use by teachers and students.